Segregation analysis of dominant osteogenesis imperfecta in Italy. Issue 6 (June 1990) - Mottes, M; Cugola, L; Cappello, N; Pignatti, P F
Abstract : We have performed linkage analysis in seven Italian families, in which mild osteogenesis imperfecta (OI) segregated as a dominant trait, by means of six DNA restriction fragment length polymorphisms (RFLPs) of type I collagen genes. OI type I was linked to the alpha 1(I) gene (COL1A1) in two families, and to the alpha 2(I) gene (COL1A2) in one family. OI type IV segregated with COL1A2 in two families. In two OI type I families, the molecular genetic data were insufficient for exclusion of one gene. Four DNA polymorphisms were particularly informative for cosegregation analysis of OI in Italian kindreds.